ANALISIS PERBEDAAN RETURN DAN ABNORMAL RETURN SAHAM SEBELUM DAN SETELAH ADANYA PROTES DARI GREENPEACE TENTANG SAMPAH PLASTIK PADA PT. UNILEVER - Hotimah, Husnul; Astawinetu, Erwin Dyah (JEM17: Jurnal Ekonomi Manajemen, 2020)
This study aims to determine the differences in the returns and abnormal returns of PT Unilever shares before and after the protest from Greenpeace in March 2019 about plastic waste that is found mostly from Unilever products. This research design uses quantitative methods with a descriptive-comparative approach. The type of data used is quantitative data and data sources used are secondary data. The analytical method used is descriptive statistics and paired sample t-test to test the hypothesis. The observation period was 21 days, 10 days before and 10 days after the protest from Greenpeace. The results of this study indicate there are no significant differences in stock returns and abnormal returns at PT. Unilever. This shows that the protest from Greenpeace does not contain information content and is not important information for investors.Kata Kunci : Return, Abnormal Return, Saham, Sampah Plastik, Greenpeace.